Car manufacturers and global road safety: a word frequency analysis of road safety documents. Issue 5 (3rd October 2006) - Roberts, I; Wentz, R; Edwards, P
Abstract : Objective: The World Bank believes that the car manufacturers can make a valuable contribution to road safety in poor countries and has established the Global Road Safety Partnership (GRSP) for this purpose. However, some commentators are sceptical. The authors examined road safety policy documents to assess the extent of any bias. Design: Word frequency analyses of road safety policy documents from the World Health Organization (WHO) and the GRSP. Main outcome measures: The relative occurrence of key road safety terms was quantified by calculating a word prevalence ratio with 95% confidence intervals. Terms for which there was a fourfold difference in prevalence between the documents were tabulated. Results: Compared to WHO's World report on road traffic injury prevention, the GRSP road safety documents were substantially less likely to use the words speed, speed limits, child restraint, pedestrian, public transport, walking, and cycling, but substantially more likely to use the words school, campaign, driver training, and billboard. Conclusions: There are important differences in emphasis in road safety policy documents prepared by WHO and the GRSP. Vigilance is needed to ensure that the road safety interventions that the car industry supports are based on sound evidence of effectiveness.